The world economy after the coronavirus shock: Restarting globalization? - Gabriel Felbermayr (Institut für Weltwirtschaft (IfW), 2020)
The COVID-19 virus has spread to 215 countries, virtually covering all areas of the world, and has plunged the world in a health emergency. The virus and the infection control measures by governments have an enormous, worldwide economic impact: when countries are connected by trade in goods, when a lockdown closes factories in one place of the world, essential inputs go missing in other places. And when a corona-induced recession hits one country, or when that area closes its borders for precautionary reasons, sales of goods or receipts from tourism by other countries go down, driving them into an economic crisis even when their own infection rates may be low. In this volume, edited by Gabriel Felbermayr, researchers from the Kiel Institute and from outside the institute provide answers to the pressing questions: How does the crisis change our world? Will there be lasting effects on our economies and on our societies at large? What does this mean for the worldwide living conditions? In this volume, they shed light on these questions from various angles, but always maintaining the global perspective. – – Das COVID-19-Virus hat praktisch alle Regionen der Welt erfasst und damit einen globalen gesundheitlichen Notstand ausgelöst. Das Virus und die Maßnahmen der Regierungen zur Eindämmung der Infektion haben enorme Auswirkungen auf die Weltwirtschaft: Wenn Länder durch Warenhandel miteinander verbunden sind, wenn zur Infektionsbekämpfung Fabriken an einem Ort der Welt geschlossen werden, dann gehen wichtige Vorleistungen an anderen Orten verloren. Und wenn in einem Land die Corona-Maßnahmen eine Rezession zur Folge haben oder wenn ein Land seine Grenzen aus Vorsichtsgründen schließt, gehen die Warenverkäufe oder Einnahmen aus dem Tourismus anderer Länder zurück und treiben diese in eine Wirtschaftskrise, selbst wenn ihre eigenen Infektionsraten niedrig sein mögen. In diesem Band, der von Gabriel Felbermayr herausgegeben wird, geben Forscher des Instituts für Weltwirtschaft und von außerhalb des Instituts Antworten auf die drängenden Fragen: Wie verändert die Krise unsere Welt? Wird diese dauerhafte Auswirkungen auf unsere Volkswirtschaften und auf unsere Gesellschaften haben? Was bedeutet die Krise für die weltweiten Lebensbedingungen? In diesem Band werden diese Fragen aus verschiedenen Blickwinkeln beleuchtet, aber immer unter Beibehaltung der globalen Perspektive.
Keywords: 330; Coronavirus; Internationale Wirtschaft; Wirtschaftskrise; Globalisierung; Wirkungsanalyse